Avaliação podocitária em casos de nefropatia diabética - MARTINS, Ana Luisa Monteiro dos Santos (2021)
Introduction: Diabetic nephropathy (DN) is the leading cause of chronic kidney disease and end-stage renal failure in the world. Several mechanisms are involved in the pathogenesis of this disease, which culminate in morphological changes, such as podocyte injury. Although the diagnosis of DN, as well as its pathogenesis, is complex, attempts to establish new biomarkers and participants in this type of lesion are still scarce. The Mindin protein has been reported, in greater quantities, in the urine of individuals with type 2 diabetes mellitus. Thus, the objective of this study was to evaluate the potential biomarker of Mindin protein in renal biopsies of patients with DN, as well as to correlate with the clinical-epidemiological characteristics and glomerular ultrastructural changes. Methods: 51 biopsies with diagnosis of DN were used and evaluated for in situ expression of WT1, which is a podocyte marker, and Mindin by immunohistochemistry. The erasure of the pedicels and the thickness of the glomerular basement membrane were analyzed under transmission electron microscopy. The control group consisted of 23 cases of kidneys from autopsies of adult patients whose cause of death was not related to infectious disease and previous renal disorders. Results: A decrease in the density of podocytes and an increase in the expression of Mindin was observed in cases of DN independent of the classes. However, there was no significant correlation between Mindin's expression and WT1. Podocytes from patients in the ND group had greater pedicle width compared to the control group and from these data we obtained a positive correlation between Mindin and pedicle erasure, in class III (p = 0.0349). The thickness of the glomerular basement membrane in the ND group was significantly greater than the control group. However, there was no significant correlation between the thickness of the glomerular basement membrane and the erasure of the pedicels. We obtained a ROC curve, with an ideal cutoff point in 5,178% of the area marked by the Mindin protein antibody, with a sensitivity of 68%, specificity of 86.96% and an AUC of 0.8687. Conclusion: The results suggest that Mindin can be considered a potential biomarker of podocyte lesion in DN.